Multiple Symmetric Lipomatosis: New Classification System Based on the Largest German Patient Cohort. Issue 4 (April 2018) - Schiltz, Daniel; Anker, Alexandra; Ortner, Christine; Tschernitz, Sebastian; Koller, Michael; Klein, Silvan; Felthaus, Oliver; Schreml, Julia; Schreml, Stephan; Prantl, Lukas
Abstract : Background: Multiple symmetric lipomatosis (MSL) is defined as a disorder of nonencapsulated adipose tissue growth. Its prevalence is indicated as 1:25, 000 and affects, as stated in the literature, mainly Mediterranean males (male:female ratio of 15:1). Phenotypes are still classified as defined by Donhauser in 1991. We report clinical and phenotypic data of the largest patient cohort investigated in Germany so far. Methods: Forty-five patients diagnosed with MSL at the University Hospital Regensburg between 2007 and 2017 were photographed, clinically examined, and blood samples were taken. Based on the photographs (n = 33), 11 independent observers assessed patients using the Donhauser classification. Furthermore, the bodies of all patients were subdivided into 12 body areas, and the viewers had to indicate all MSL-affected areas per patient. Prevalence was calculated, comorbidities were assessed, and blood samples were analyzed. Results: According to the established Donhauser classification, less than 50% of the patients could be classified. Therefore, based on the constellations of MSL-affected body areas, a new classification that divides phenotypes of MSL into 5 types (Ia, Ib, Ic, II, and III) was set up and was able to cover 100% of our patients. The male to female ratio was found to be 1:2.5 (male:female). Prevalence of MSL in the catchment area was found to be 1:25, 000. Hypercholesterinemia and hypothyroidism were frequent comorbidities, and blood analyses were normal besides a hypercholesterinemia. Discussion: The new proposed classification system describes 5 subtypes and allowed to classify all assessed patients. Male to female ratio (1:2.5) contradicted most previous publications.